2010
DOI: 10.1111/j.1349-7006.2010.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐10b regulates tumorigenesis in neurofibromatosis type 1

Abstract: MicroRNAs (miRNAs) are frequently deregulated in human tumors, and play important roles in tumor development and progression. The pathological roles of miRNAs in neurofibromatosis type 1 (NF1) tumorigenesis are largely unknown. We demonstrated that miR-10b was up-regulated in primary Schwann cells isolated from NF1 neurofibromas and in cell lines and tumor tissues from malignant peripheral nerve sheath tumors (MPNSTs). Intriguingly, a significantly high level of miR-10b correlated with low neurofibromin expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 44 publications
2
68
0
10
Order By: Relevance
“…It has been reported that miR-10b was upregulated in all glioma samples compared with nonneoplastic brain tissues; the expression level of miR-10b was associated with higher-grade glioma and the tumor invasive factors uPAR and RhoC [9]. Moreover, the overexpression level of miR-10b was observed in many other cancers, including neurofibromatosis type 1, esophageal cancer, pancreatic cancer, nasopharyngeal carcinoma, hepatocellular carcinoma, and colorectal cancer [11][12][13][14][15][16]. These findings suggested that miR-10b was strongly expressed in highly metastatic cancer cells and played a central role in cancer metastasis.…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that miR-10b was upregulated in all glioma samples compared with nonneoplastic brain tissues; the expression level of miR-10b was associated with higher-grade glioma and the tumor invasive factors uPAR and RhoC [9]. Moreover, the overexpression level of miR-10b was observed in many other cancers, including neurofibromatosis type 1, esophageal cancer, pancreatic cancer, nasopharyngeal carcinoma, hepatocellular carcinoma, and colorectal cancer [11][12][13][14][15][16]. These findings suggested that miR-10b was strongly expressed in highly metastatic cancer cells and played a central role in cancer metastasis.…”
Section: Introductionmentioning
confidence: 93%
“…Function of miR-10b has mainly been studied in breast cancer. In vitro it has been shown to promote migration and invasion in breast and esophageal cancer cell lines, as well as malignant peripheral nerve sheath tumor cell lines (51,57,58). In vivo studies also highlight the importance of miR-10b in metastasis, since mice treated systemically with antagomiR-10b developed less metastasis than their non-treated counterparts (59).…”
Section: Discussionmentioning
confidence: 99%
“…53,59 A recent study has shown that a microRNA, miR-10b, may regulate NF1 tumorigenesis by targeting the NF1 mRNA 3= untranslated region and modulating the Ras signaling pathway. 64 In general, microRNAs hybridize to the 3= untranslated region of target mRNAs and can repress mRNA translation or mediate its cleavage.…”
Section: Regulation Of Nf1 Gene Expressionmentioning
confidence: 99%